Velocity models inferred from p-waves travel time curves in south Aegean - Nikolintaga, I.; Karakostas, V.; Papadimitriou, E.; Vallianatos, F.; Panopoulou, G. (Bulletin of the Geological Society of Greece, 2007)
The seismicity recorded during Ist January to 31st August 2005 from a new telemetry network installed and operating on the island of Crete, is used in an effort to obtain new velocity models for the area of south Aegean. The models are constructed from the P-waves travel time curves and are later used for the events relocation with the HYPOINVERSE algorithm and station delays calculation. Furthermore, results are discussed and compared with the ones derived from other significant previous works presented the last years. We anticipate by combining all the available information from the literature and the analysis of our data set to contribute to the seismotectonic modeling of the study area and to construct a most complete image of the geometry of the subducted plate.